EFEKTIFITAS PELAKSANAAN PERATURAN PEMERINTAH NOMOR 45 TAHUN 1990 TENTANG PERKAWINAN DAN PERCERAIAN TERHADAP PERKAWINAN POLIGAMI BAGI PEGAWAI NEGERI - Haryani Sulistyowati (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2016)
The polygamy attacks the life of Indonesian civil servants. This phenomenon, probably, has been taken place by the remuneration. Mostly, the polygamy is committed without any permission of wife, official marriage, and marriage according to the religious or underhand marriage. We justify all of this by speaking of such civil servants as having broken the law or having failed to meet their obligation This violation brings some legal consequences such as disciplinary sanctions according to article 7 of Government Regulation of No. 53 of 2010 on Discipline Civil Servants. By virtue of the criminal law, he who hides the origin of his marriage can be subject to criminal sanctions as stipulated in the chapter XIII of the Indonesian Criminal Code, mainly articles 277-280. This research based on the sociological perspective analyzes two legal issues, i.e. what are the factor hampering the implementation and how to optimize of Government Regulation No. 45 of 1990.